Trends in uptake of early infant diagnosis for HIV: implementation results of the Ugandan military PMTCT program - Lubega, Paul; Lawoko, Stephen; Akatukunda, Filbert; Seruwagi, Gloria; Ninsima, John Bosco; Gahurra, Lydia; Lugada, Eric; Akao, Juliet; Asiimwe, Evelyn; Wamundu, Cassette; Ssemmanda, Robert; Kikaire, Ben; et al. (International Journal Of Community Medicine And Public Health, 2021)
Background: Early infant diagnosis (EID) is an important strategy of the Prevention of Mother-to-child transmission (PMTCT) and when implemented in combination with other strategies could eliminate HIV MTCT. We implemented a series of strategic interventions intended to improve EID at 9 Military facilities in Uganda and evaluated their impact on uptake of EID. Methods: A retrospective cross-sectional design was adopted, following-up HIV Exposed Infants (HEI) at the study sites over a 2 year period, and using a data extraction tool to capture4 indicators of EID namely; number of HIV-positive mothers, number of HEI enrolled, number of PCR and rapid tests performed on HEI, and number of HIV-positive results of HEI. Scatter plots and simple linear regression were applied to demonstrate trends in EID uptake and estimate intervention impact over time. Statistical significance was assumed at p<0.05. Results: We established incremental trends in numbers of first PCR (f [1,6]=2.8; p=0.15),third PCR (f [1,6]=8.4; p<0.05), rapid tests (f [1,6]=16.1; p<0.05) performed on HEI, and a modest decline in HIV-positivity among HEI over the study period. The intervention improved retention in PMTCT cascade to 80%, when contrasted with the national average of 70%. Conclusions: We have demonstrated that interventions invoking pre-booking HIV-positive pregnant mothers during antenatal care, follow up of mother-baby pairs using telephone and mentor mothers and integrating EID in immunization programs can improve uptake of EID in a relatively short period, and with a positive impact on EID indicators.